Seepage, depth, and oxygen as drivers of heterogeneity and resilience of carbonate macrofauna at methane seeps - Pereira, Olívia Soares (2025)
Much of the variability in methane seep macrofaunal communities has been attributed to seepage activity (i.e., fluid flux regime); however, more attention is needed to other environmental factors that might be playing a role in structuring methane seep communities. A primary goal was to understand how depth and bottom-water dissolved oxygen concentration affect the influence of seep activity on the diversity and trophic structure of carbonate macrofauna and their recovery and resilience. We conducted mensurative and manipulative experiments on the Costa Rican Pacific margin at three seep locations with varied hydrographic conditions: (1) Quepos Landslide, at 400 m deep, within the oxygen minimum zone (OMZ); (2) Mound 12, at 1,000 m deep, just below the OMZ; and (3) Jaco Scar, at 1,850 m deep, well below the OMZ. Within locations, experiments were conducted at active, transition, and background seep habitats. Habitat was the main factor influencing macrofauna at the deeper seeps, where chemosynthetic production supplies the primary food source. Seep-specialist species found in active habitats exhibited faster responses to colonization and transplant experiments mimicking seep activation than species found in transition habitats. Species in transition habitats, relying on both photo- and chemosynthetic production, appeared to have higher recovery and resilience rates in experiments mimicking seep cessation than seep specialists. Within the OMZ, low oxygen conditions overrode the effects of habitat, yielding low densities and low diversity to the point of limiting colonization and community retention, as observed through manipulated changes in seep habitat. Our study highlights how environmental factors (i.e., seep habitat, depth, and oxygen concentration) promote macrofaunal heterogeneity on carbonates at methane seeps and might control resilience. With the expansion of OMZs and seeps due to ocean deoxygenation and warming, respectively, an understanding of how environmental factors affect the resilience and recovery of these communities is important.